Kesurupan Massal di Sekolah Menengah: Kerasukan Roh Jahat atau Emotional Contagion? - Imaduddin Hamzah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2021)
This study aims to explore the phenomenon of mass trance in middle school. Previous studies in trance focused in individual psychological factors and view the trance as psychological disorder (hysteria). Mass trance shows behavior and emotion performed by students through interaction process. Thus, this phenomenon is not only viewed from clinical perspective, but also social psychology explanation. This study used grounded theory by performing interview on 17 informants (students and teachers) in a school with mass trance cases in Jakarta and Tangerang, and analysis on 31 video recordings about the online news on trance cases. The findings show that there are seven categories of factors on mass trance: emotional stimulus, mystical experiences, suggestability, supernatural interpretation, anomalous experience, unconditioned emotional response, and mimicry. Core category analysis shows that mass trance on middle school students indicates emotional contagion with supernatural beliefs nuance.